2022
DOI: 10.3389/fphar.2022.894285
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Gallate Suppresses the Migration, Invasion, and Epithelial-Mesenchymal Transition of Hepatocellular Carcinoma Cells via the AMPK/NF-κB Signaling Pathway in vitro and in vivo

Abstract: Methyl gallate (MG), a polyphenolic compound found in plants, is widely used in traditional Chinese medicine. MG is known to alleviate several cancer symptoms. However, most studies that have reported the antitumor effects of MG have done so at the cellular level, and the inhibitory effect and therapeutic mechanism of MG in hepatocellular carcinoma (HCC) have not been extensively explored in vivo. We aimed to understand the therapeutic mechanism of MG in HCC in vitro and in vivo. MTT and colony formation assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Studies on the cytotoxic effects of MG demonstrated that this phytochemical elicits remarkable cell viability inhibition in many tumor systems [ 29 , 31 ]. However, since no data are available for colon cancer, we undertook a study aimed at evaluating the MG antitumor potential on the viability of two colon cancer cell lines (HCT116 and Caco-2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the cytotoxic effects of MG demonstrated that this phytochemical elicits remarkable cell viability inhibition in many tumor systems [ 29 , 31 ]. However, since no data are available for colon cancer, we undertook a study aimed at evaluating the MG antitumor potential on the viability of two colon cancer cell lines (HCT116 and Caco-2).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, MG was also shown to exert a tumor inhibitory effect in in vitro and in vivo mouse models of hepatocellular carcinoma. Furthermore, it did not exert any cytotoxic effect in human normal hepatocytes, while it significantly suppressed the migration, invasion and epithelial–mesenchymal transition in tumor systems of HCC via the AMPK/NF-κB pathway [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gliclazide induces AMPK activation and inhibits vascular smooth muscle cell proliferation in a dose- and time-dependent manner [ 9 ]. AMPK-NF-κB signaling participates in the pathogenesis of non-alcoholic fatty liver disease, non-alcoholic steatohepatitis, and hepatocellular carcinoma by regulating proliferation, migration, and invasion [ 10 , 11 ]. However, it is unknown whether gliclazide regulates AMPK-NF-κB signaling in CAC.…”
Section: Resultsmentioning
confidence: 99%
“…Methyl gallate can exert pharmacological effects through multiple pathways and targets, such as PI3K-Akt, ERK1-2, Caspase, AMPK-NFkB, Wnt-β-catenin, TLR4-NF-kB, MAPK, p53, NLRP3, ROS, EMT (Liang et al 2023). It is thus possible that the reduction of the leishmaniotic lesion and the parasitic load in our study in the golden hamsters treated with the methyl gallate microemulsion on its own or in combination with Glucantime ® may be related to activation or deactivation of any of these pathways.…”
Section: Discussionmentioning
confidence: 99%